Implementations of Autonomous Maintenance to Relieve Stoppages on PT NIKF – Sachet Packaging Chain - Sukanta; R. Maulana; Sari, Dessy Agustina (IPTEK The Journal for Technology and Science, 2025)
Autonomous maintenance taught operator to keep devices, create cooperation each employer and did problem solving that occurring in machine. This research described assembling of autonomous maintenance on PT NIKF – minor stoppages trouble in sachet production line. Our team used the OEE method to know the latest line condition and variety losses that causing the performance were not optimal. After that, the next steps were using visual losses map and diagram Pareto to get the detail (component with many losses). By Go See Think Do, the researcher could find much maintenance that must be done in SIC line 1. Through the application, this effort could reduce the losses of minor stoppages - 79,52%.